Xanthohumol ameliorates Diet-Induced Liver Dysfunction via Farnesoid X Receptor-Dependent and Independent Signaling - Paraiso, Ines L.; Tran, Thai Q.; Magana, Armando Alcazar; Kundu, Payel; Choi, Jaewoo; Maier, Claudia S.; Bobe, Gerd; Raber, Jacob; Kioussi, Chrissa; Stevens, Jan F. (Frontiers in Pharmacology, 2021)
The farnesoid X receptor (FXR) plays a critical role in the regulation of lipid and bile acid (BA) homeostasis. Hepatic FXR loss results in lipid and BA accumulation, and progression from hepatic steatosis to nonalcoholic steatohepatitis (NASH). This study aimed to evaluate the effects of xanthohumol (XN), a hop-derived compound mitigating metabolic syndrome, on liver damage induced by diet and FXR deficiency in mice. Wild-type (WT) and liver-specific FXR-null mice (FXRLiver-/-) were fed a high-fat diet (HFD) containing XN or the vehicle formation followed by histological characterization, lipid, BA and gene profiling. HFD supplemented with XN resulted in amelioration of hepatic steatosis and decreased BA concentrations in FXRLiver-/- mice, the effect being stronger in male mice. XN induced the constitutive androstane receptor (CAR), pregnane X receptor (PXR) and glucocorticoid receptor (GR) gene expression in the liver of FXRLiver-/- mice. These findings suggest that activation of BA detoxification pathways represents the predominant mechanism for controlling hydrophobic BA concentrations in FXRLiver-/- mice. Collectively, these data indicated sex-dependent relationship between FXR, lipids and BAs, and suggest that XN ameliorates HFD-induced liver dysfunction via FXR-dependent and independent signaling.